Analisis Profesionalisme Guru di SMK Negeri 1 Kota Padang - Endang Gustina; Anisah Anisah (Jurnal Bahana Manajemen Pendidikan, 2020)
This research is based on Teacher Professionalism at SMK 1 Padang which still needs to be improved. The objectives of this study are (1) Knowing teacher perceptions about the desire to always display behaviors that approach the ideal standards of professionalism of teachers at SMK Negeri 1 Padang; (2) Knowing teacher perceptions about improving and maintaining the professional image in teacher professionalism at SMK 1 Padang; (3) Knowing teachers' perceptions about always pursuing opportunities to develop professions that can improve and improve the quality of professional knowledge and skills of teachers in SMKN 1 Padang; (4) Knowing teacher perceptions about the pursuit of quality and ideals in the existing profession of teacher professionalism at SMK 1 Padang; (5) Knowing teachers' perceptions about having pride in their profession in the professionalism of teachers at SMK 1 Padang. This type of research is descriptive. The population of this study was 172 teachers of SMK Negeri 1 Padang. The sampling technique in this study was Simple Random Sampling, sampling using the Slovin formula so that the number of samples obtained was 64 people. Data collection tool in this study is a questionnaire in the form of a Likert Scale with five alternative answers that have been tested for validity and reliability. Data were analyzed using the mean formula and the percentage formula. The results showed that the professionalism of teachers at SMK 1 Padang from various aspects had an average percentage of 82.83% in the good category. Then it can be concluded that the professionalism of teachers at SMK 1 Padang is good.